Gastric duplication 20 years after a partial distal gastrectomy: a case report and review of literature - Feng Y; Ye JN; Chen CQ; Zhang XH (Dove Medical Press, 2019)
Yun Feng, Jin-Ning Ye, Chuang-Qi Chen, Xin-Hua ZhangThe Center for Gastrointestinal Surgery, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, 510080, People’s Republic of ChinaAbstract: Gastric duplications are the least common gastrointestinal duplications, especially in adults. Duplication cyst with an accessory pancreatic lobe is extremely rare and is even more uncommon in the setting of polysplenia. No gastric duplication after partial gastrectomy has been reported. We present a 41-year-old male diagnosed with gastric duplications with an accessory pancreatic lobe and polysplenia. Another characteristic of this case is partial gastrectomy 20 years ago without the discovery of duplication cysts. The gastric duplications, accessory pancreatic lobe and accessory spleen were successfully resected.Keywords: gastric duplication, polysplenia, accessory pancreatic lobe, gastrectomy, adult